Policy Evaluation Through West Java Provincial Regulation No. 1 of 2021 on the Facilitation of Pesantren Administration: Case Study at Pondok Pesantren Cibereum Kidul, Cimahi - Dini Nadila; Yaya Mulyana (Jurnal Ilmiah Multidisiplin Indonesia (JIM-ID), 2025)
Facilitating the administration of pesantren in accordance with their traditions and unique characteristics is essential. Therefore, the Government of West Java is expected to support and strengthen the role and contribution of pesantren within the province, as stipulated in West Java Provincial Regulation No. 1 of 2021. In Cimahi City, however, not all pesantren have received such facilitation from the government, including Pondok Pesantren Cibereum Kidul. Inadequate facilities reduce the attractiveness of a pesantren compared to other educational institutions. Consequently, pesantren with insufficient facilities tend to lag behind, lose public interest, and experience a decline in service quality for their santri (students). This study aims to: a) Evaluate the policy implementation of West Java Provincial Regulation No. 1 of 2021 concerning pesantren facilitation at Pondok Pesantren Cibereum Kidul, Cimahi. b) Determine whether Pondok Pesantren Cibereum Kidul has received government facilitation support. c) Identify obstacles in implementing the regulation.